2023
DOI: 10.7717/peerj.15121
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of clarithromycin-resistant Helicobacter pylori isolates: a systematic review and meta-analysis

Abstract: Background Knowledge of global clarithromycin (CLA)-resistant rates of Helicobacter pylori (H. pylori) is crucial for decision of the most appropriate eradication therapies with good clinical outcomes. Therefore, this review and meta-analysis aimed to evaluate the global prevalence of the CLA resistance in H. pylori to provide some guidance for selecting the first-line antibiotics. Method A comprehensive search was performed for relevant literature until April 2021 in PubMed, Embase, and Web of Science datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 260 publications
0
6
0
Order By: Relevance
“…Studies have reported an increase in resistance to clarithromycin and rifampicin in H. pylori over the past decades. [57][58][59][60] Concerning clarithromycin and rifampicin resistance, we further visualized the metabolic differences between H. pylori-sensitive and -resistant strains to these antibiotics. This was achieved by generating GSMMs for each strain and performing a comprehensive survey of pathway analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported an increase in resistance to clarithromycin and rifampicin in H. pylori over the past decades. [57][58][59][60] Concerning clarithromycin and rifampicin resistance, we further visualized the metabolic differences between H. pylori-sensitive and -resistant strains to these antibiotics. This was achieved by generating GSMMs for each strain and performing a comprehensive survey of pathway analysis.…”
Section: Discussionmentioning
confidence: 99%
“…[ 10,14,26 ] High levels of CLA resistance may stem from several factors including the unregulated prescription of CLA and the utilization of CLA in treating other infections like respiratory tract infections or intestinal parasite infections. [ 34 ]…”
Section: Discussionmentioning
confidence: 99%
“…The global resistance rate of clarithromycin increased significantly from 24.28% in 2010–2017 to 32.14% in 2018–2021 with Switzerland, Portugal, and Israel having the highest resistance rate [ 25 ]. Similarly, clarithromycin resistance in Malaysia is also increasing from 6.8% between July 2011 and August 2012 [ 26 ] to 35.6% between April 2014 and August 2015 [ 27 ].…”
Section: Discussionmentioning
confidence: 99%